MEKANISME DEPOSITO DENGAN METODE AUTOMATIC ROLL OVER PADA PT. BANK ACEH SYARIAH KANTOR CABANG PEMBANTU (KCP) BALAI KOTA BANDA ACEH - Heri Syaputra; Saiful Bahgia (JURNAL KREASI RAKYAT, 2024)
The Deposit Mechanism is a stage carried out or implemented by a company to explain deposits regularly and systematically to provide services to make it easier for customers to invest deposit funds. The Deposit Mechanism is contained in the SOP that has been established so that all activities in a company run smoothly. This research aims to find out how the Deposit Mechanism with Automatic rollover is implemented by PT Bank Aceh Syariah Sub Branch Office (KCP) Banda Aceh City Hall which is given to its customers. In conducting this research, the researcher used a qualitative descriptive research method to find out what the Automatic Roll Over Deposit Mechanism is and also to get clear information about each indicator that will be studied, especially those related to deposits. The data collection techniques used in this research are primary and secondary data types. The data collection methods used were interviews, observation, and documentation. Judging from the research results obtained by the author, it can be concluded that the Deposit Mechanism with Automatic Roll Over implemented by PT Bank Aceh Syariah Sub Branch Office (KCP) Banda Aceh City Hall has been running quite well, this is indicated by the existence of an SOP regarding the deposit mechanism which are determined and implemented by PT Bank Aceh Syariah are in line with statutory regulations and do not conflict legally or theoretically. However, in this case, PT Bank Aceh Syariah must maintain and maintain the quality of service so that it continues to run well and can continue to improve the quality of service, especially regarding the deposit mechanism so that it can run even better.